2016
DOI: 10.5897/ajfs2016.1439
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pattern and nutritional status of primary school pupils in a South Western Nigerian state: A rural urban Comparison

Abstract: Nutrition may be defined as the process, act, or study of how living things use nutrients for energy, growth, and maintenance. Contrary to widely held notions, malnutrition may be caused by people choosing to eat the wrong types of food, rather than a lack of what to eat. The objectives of the study were to describe the dietary pattern of primary school pupils in an urban and rural local government area of Lagos State, Nigeria and to examine the relationship between dietary pattern and prevalence of malnutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The prevalence of underweight was higher among pupils residing in the rural areas of the metropolis compared to those residing in urban areas though not statistically significant. Similar observation had been reported in previous studies [38][39][40]. In this study, underweight was not found in pupils attending private schools, however, in Uyo, 27.3% of the pupils attending private schools were underweight [41].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of underweight was higher among pupils residing in the rural areas of the metropolis compared to those residing in urban areas though not statistically significant. Similar observation had been reported in previous studies [38][39][40]. In this study, underweight was not found in pupils attending private schools, however, in Uyo, 27.3% of the pupils attending private schools were underweight [41].…”
Section: Discussionsupporting
confidence: 91%
“…Lower prevalence has however been reported in a neigbouring state among urban dwellers [34,35]. Other studies in Nigeria [5,32,37,38], Ghana [22], Ethiopia [6,7] and India [16] have reported higher prevalence of underweight.…”
Section: Discussionmentioning
confidence: 92%